Interview with Liz Millward: Why New Zealand? - Roth, Jennifer (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
Roth joins in conversation with Liz Millward, an Associate Professor in the Women’s and Gender Studies Program at the University of Manitoba and the 2009 CWSA/ACÉF Book Prize Winner.